Penerapan Media Pembelajaran Animasi Dalam Meningkatkan Minat Belajar Siswa Pada Materi Norma Dan Macam-Macam Norma Di Kelas XI SMK Negeri 3 Takengon - Fitri, Ernida; Kaban, Tampilen; Kesuma, Sapta (Toga Jurnal Keguruan dan Ilmu Pendidikan, 2024)
This study aims to determine whether the use of animated media can increase student learning interest in the material of norms and various norms in Class Xl SMK Negeri 3 Takengon. The research method in this study is quantitative experimental type. The population in the study was class XI TBSM SMK Negeri 3 Takengon in sampling using purposive sampling, the sample selected was class XI tbsm 1, as the experimental class and class XI tbsm 2 class as the control class. The data collection techniques used are observation techniques, multiple choice question tests, and the data analysis technique used in this study is to see the percentage of classical completeness in each class. The results showed that: Learning outcomes showed a significant increase by using learning media in the form of animated videos. In the control class itself, the percentage of class completeness at the first cycle stage was 50% complete and 50% incomplete, while in the experimental class the percentage of completeness was 60% complete and 40% incomplete. Furthermore, in the second cycle stage, there was an increase, namely, in the control class the percentage level of classical completeness was 85% complete and 15% incomplete, while in the experimental class the percentage level of classical completeness was 90% complete and 10% incomplete. Therefore, the hypothesis that has been made by researchers can be answered that there is a significant effect of using animated learning media to increase student learning interest in PPKN subjects at SMK NEGERI 3 Takengon.